2010
DOI: 10.1007/s10658-010-9659-0
|View full text |Cite
|
Sign up to set email alerts
|

The structure of Phytophthora infestans populations from organic and conventional crops

Abstract: The characteristics of populations of Phytophthora infestans from organic farms, small conventional farms and large conventional farms were determined from isolates collected in northern Estonia in 2004 and 2005. For the population as a whole 41% were A2; all virulence factors to the 11 R genes from Solanum demissum were found; and more than 70% had high or intermediate resistance to metalaxyl. Isolates from organic farms tended to have more complex pathotypes than isolates from either large or small conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Furthermore, the predominance of metalaxyl-sensitive isolates observed in small conventional fields compared to large-scale conventional farming reflects the significant effect of a cultivation system on the selection pressure of a pathogen population, altering the sensitivity levels to active ingredients [ 74 , 89 , 90 , 91 ]. Runno-Paurson et al [ 94 ], recorded a higher proportion of metalaxyl-resistant isolates in large conventional farms compared to small conventional farms, which was also observed in this study. A similar result was also reported by Brylinska et al [ 92 ] and Cooke et al [ 95 ].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the predominance of metalaxyl-sensitive isolates observed in small conventional fields compared to large-scale conventional farming reflects the significant effect of a cultivation system on the selection pressure of a pathogen population, altering the sensitivity levels to active ingredients [ 74 , 89 , 90 , 91 ]. Runno-Paurson et al [ 94 ], recorded a higher proportion of metalaxyl-resistant isolates in large conventional farms compared to small conventional farms, which was also observed in this study. A similar result was also reported by Brylinska et al [ 92 ] and Cooke et al [ 95 ].…”
Section: Discussionsupporting
confidence: 88%
“…The Polish population of P. infestans , unlike the French, British or Dutch populations (Montarry et al ., ; Cooke et al ., ; Li et al ., 2012b), remained diversified, with low frequency of the A2 mating type, rare metalaxyl resistance and no single invasive genotypes spreading. It resembled more closely P. infestans populations in the Nordic countries (Denmark, Finland, Norway and Sweden; Brurberg et al ., ) and Estonia (Runno‐Paurson et al ., ), with the majority of isolates of mating type A1 and high genetic variation.…”
Section: Discussionmentioning
confidence: 97%
“…Domination of Ia mitochondrial haplotype is also common in other European populations of P. infestans , and IIa is widespread, but with a lower frequency. However in Estonia Ia and IIa haplotypes are found in a ratio close to 1:1 (Runno‐Paurson et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major concern to get a pure culture of Phytophthora is possible the presence of fast-growing organisms such as Pythium other genera of fungi, which affected the growth of Phytophthora (Canaday and Schmitthenner, 1982). As well, the material of potato seed can affect the fungal co mmunity in the fields (Runno-Paurson et al, 2010b, Drenth et al, 2001Lal et al, 2015). In the present study, morphological characters of sporangial size was undistinguished which was found to be high values of aggressive isolates.…”
Section: Culture Media Evaluationmentioning
confidence: 99%